Peningkatan Kepuasan Konsumen: Promosi dan Kepercayaan pada Layanan Kurir PT. POS Indonesia (Persero) Cabang Parepare - Paulus, Ekking; Muslimin, Ulyana; Alimuddin, Firman (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine promotion and trust have a partial effect on consumer satisfaction in using courier services at PT. Pos Indonesia (Persero) Parepare Branch. To find out promotion and trust influence simultaneously on consumer satisfaction in using courier services at PT. Pos Indonesia (Persero) Parepare Branch. The analytical method used is descriptive quantitative, using primary data sourced from the results of the questionnaires that have been answered by the respondents. The tests used include validity test, reliability test, descriptive analysis, multiple linear regression analysis and t test (partial), F test (simultaneous), R2 test (coefficient of determination). These results indicate that promotion has no partial effect on consumer satisfaction in using courier services at PT. Pos Indonesia (Persero) Parepare Branch, trust has a partial effect on consumer satisfaction in using courier services at PT. Pos Indonesia (Persero) Parepare Branch. Promotion and trust have a simultaneous effect on consumer satisfaction in using courier services at PT. Pos Indonesia (Persero) Parepare Branch.